GE_GERICHTE P/3259/2014 vom 25. Juli 2017 - GE Cour de justice (2017)
RIXE; LÉSÉ; PARTIE CIVILE; FRAIS JUDICIAIRES ; ACTION EN RESPONSABILITÉ ; TORT MORAL | CP.133; CPP.115; CPP.122; CPP.126; CPP.426; CPP.428; CPP.433; CO.41; CO.47